1993
DOI: 10.1111/j.1365-2702.1993.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the prevalence and psychological sequelae of sexual harassment of nursing staff

Abstract: Summary A pilot study of nurses and nursing auxiliaries was carried out to determine the prevalence and psychological sequelae of sexual harassment. Thirteen nurses and 22 nursing auxiliaries were interviewed. Sixty per cent reported having experienced sexual harassment on at least one occasion. The results showed that the predominant experience typically occurred: to female nursing staff; by male patients; on the wards; often while washing patients. There was minimal reporting of the incident. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…In the nursing context, sexual harassment has been largely considered a separate issue to violence and aggression and studies of sexual harassment do not always include an examination of patients as perpetrators (Finnis et al . , Leiter et al . , Valent & Bullough , Celik et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nursing context, sexual harassment has been largely considered a separate issue to violence and aggression and studies of sexual harassment do not always include an examination of patients as perpetrators (Finnis et al . , Leiter et al . , Valent & Bullough , Celik et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the place of gender in shaping organizational relationships, power dynamics and oppressive behaviours that enable 'insider' perpetrated violence has been explored (Roberts 2000, Speedy 2004, Strauss 2008, the gendered and sexualized nature of physical, emotional, and verbal violence and abuse directed towards nurses by those not employed in the organization has been largely overlooked (Lawoko et al 2004, Rowe & Sherlock 2005, Roche 2010). In the nursing context, sexual harassment has been largely considered a separate issue to violence and aggression and studies of sexual harassment do not always include an examination of patients as perpetrators (Finnis et al 1993, Leiter et al 2001, Valent & Bullough 2004, Celik et al 2007). Furthermore, narrow definitions of sexual violence have been adopted, with only physical acts included in the category of sexual violence in some studies (Oliveira & Flava 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses tend to be sexually harassed by patients because of the nature of their job duties: the patient's physical care. One study conducted in the United Kingdom indicated that sexual harassment of nurses often occurred while washing patients (Finnis et al, 1993). In addition, female nurses have been portrayed through the media as “sex objects” (Heinrich, 1987) or “golden‐hearted sex objects” (Savage, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were most frequently unknown. Finnis et al (1993) interviewed nursing staff in a pilot the perpetrators (87%) but doctors (67%) and workplace colleagues (59%) were also implicated. Those who were study carried out within a single unit with 100% of the staff taking part in the study.…”
Section: Problems Of Definitionmentioning
confidence: 99%